Structural Frame Analysis under Earthquakes with Various Base Flexibility: A Review (Journal of Engineering, 2025)
This literature review investigates the seismic behavior of low-rise steel structural frames with fixed, pinned, and base-isolated column bases under single and successive earthquake excitations. Experimental shaking table tests and Abaqus finite element models are utilized to evaluate the impact of base flexibility on structural performance measures, including inter-story drift, base shear, and acceleration response. Base-isolated systems, including elastomeric, lead-rubber, and friction pendulum bearings, demonstrate superior energy dissipation capacity and reduced seismic demand compared to traditional fixed and pinned bases. While pinned bases offer rotational flexibility that reduces moment concentration, they are susceptible to excessive lateral displacement in multi-story configurations. Fixed bases provide stiffness but transmit higher forces directly to the structural frame. Current research underestimates the seismic loading capability of base isolation and bracing systems, despite significant advances in isolation technology. This review identifies a critical research gap in evaluating hybrid seismic protection strategies, especially for structures subjected to multi-event ground motions. Future directions are proposed to address these challenges through integrated experimental and numerical investigations, aiming to enhance the resilience of modern buildings in earthquake-prone regions.